2014
DOI: 10.1016/j.jcrysgro.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Bridgman growth of sapphire—Seed crystal shapes and seeding characteristics

Abstract: The growth of sapphire by the traditional vertical Bridgman (VB) method was studied by using various shapes of seed crystals and tungsten (W) crucibles shaped to match the seeds. Approximately 2-inch diameter, c-axis sapphire single crystals were reproducibly grown from three kinds of seed: thin, tapered and full diameter. Factors relating seed type to single-crystal growth are discussed, including the reproducibility of seeding processes, and the generation and elimination of low-angle grain boundaries (LAGBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 12 publications
(14 reference statements)
0
11
0
1
Order By: Relevance
“…We could confirm in Fig. 7 that just as the stereographic projections of Al 2 O 3 [11][12][13][14][15][16][17][18][19][20], [0001], and YAG [001], [À 112] show the same orientations as the seed, the Ce-doped MGC grown in the Mo crucible also retained the orientation of the seed. In contrast, we found that in Ce-doped MGC grown in an Ir crucible, while the orientation of the Al 2 O 3 phase was the same as the seed, however, the orientation of the YAG phase was inclined about 131 from that of the seed.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…We could confirm in Fig. 7 that just as the stereographic projections of Al 2 O 3 [11][12][13][14][15][16][17][18][19][20], [0001], and YAG [001], [À 112] show the same orientations as the seed, the Ce-doped MGC grown in the Mo crucible also retained the orientation of the seed. In contrast, we found that in Ce-doped MGC grown in an Ir crucible, while the orientation of the Al 2 O 3 phase was the same as the seed, however, the orientation of the YAG phase was inclined about 131 from that of the seed.…”
Section: Resultsmentioning
confidence: 65%
“…The crucible was mounted on a Mo crucible rod that can rotate and also translate vertically. A W/Re thermocouple was inserted in the crucible rod to measure the temperature of the crucible bottom [18]. The carbon heater was powered by high-frequency induction coils.…”
Section: Methodsmentioning
confidence: 99%
“…Sapphire crystals, 50 mm in diameter and elongated along the c-axis, were grown by the VB technique using a tapered seed and a W crucible [11]. The furnace consisted of a graphite heater and carbon heat shields, and was filled with an atmosphere of 99.999 % pure argon gas (absolute pressure about 100kPa).…”
Section: Methodsmentioning
confidence: 99%
“…The crucible was slowly drawn downwards at 3 mm/h, the crystal growth being controlled by the rate at which the crucible was drawn down. Detailed growth conditions have been reported elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%
“…VB 공정은 기존 HEM과 비교하여 hot zone 내 온도구배와 결정성장 속도의 제어가 용이하 며 [7][8][9], 성장시 hot zone 하단에 저온부가 형성되므로 CZ, KY 등의 공정과 비교하여 대류의 영향에서 자유로 운 장점이 있다. 또한 기판에 쓰이는 c-축 방향으로 직 접 성장이 가능하고 대구경화에 용이하여 향후 LED용 사파이어 기판 제조에 적극 활용될 것으로 기대된다 [10].…”
unclassified